Poetry of Ruqshaana Kamish - Kamish, Ruqshaana (WritingThreeSixty: Journal or Research and Creative Text, 2021)
RebellionLove’s follyDisillusionedJourney towards lifeBroken wingsLeap of faithSeparate pathsMore than thisCrossing boundariesFalling into youEssence of a poetWith clearer eyesJust helloUnforgettableDestinyWorlds apartLimitlessThe edgeGreen market squareDoomed loveEchoesSins of the fatherFight for sanityI sayElements of freedomMysteryFundamental natureMelodyCanvas of lifeThe heart of mankindUtter stupidityLong forgottenLonely manCynical love